Rancang Bangun My temp (alat pendeteksi suhu badan berbasis IOT) - Muhammad, Nauval Arkan Aunillah; Nurpulaela, Lela (Jurnal Ilmiah Wahana Pendidikan, 2024)
Design and Development of My Temp (IoT-Based Body Temperature Monitoring Device). This research aims to design and develop a body temperature detection device based on the Internet of Things (IoT) called "My Temp." The device is designed to effectively and automatically measure human body temperature with high accuracy and send measurement data from ESP32 to the My Temp application. My Temp utilizes the DHT11 temperature sensor and is connected to the IoT network to enable real-time temperature monitoring. Additionally, the device is designed to be integrated with a mobile application for easy monitoring and reporting of individual or group body temperatures. This research is expected to contribute to the development of innovative health technology, facilitating efficient and reliable body temperature monitoring. The results of this research can have broad applications in public health settings, workplaces, or other public places where body temperature detection is crucial, especially in the context of controlling the spread of infectious diseases.